The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1002/(sici)1097-0185(20000301)258:3<286::aid-ar8>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Spleen of Dasypus hybridus (Mammalia, Dasypodidae): A light and electron microscopic study

Abstract: Armadillos are relictual mammals important as models for biomedical studies. They contain adaptative and primitive characteristics in both anatomical and physiological aspects. In this study we describe the splenic histology and cytology of the "mulita," Dasypus hybridus. Organ samples were processed for light and electron microscopy study. The microanatomy of the organ samples as well as their different cell types are described. The spleen is non-sinusoidal, with the typical arrangement for storage functions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…This fact agrees with the splenic structure observed in D. novemcinctus (Hayes, 1970) and D. hybridus (Galíndez et al, 2000) and differs from the observed in Z. pichiy, which shows isolated smooth muscle cells and myofibroblasts interposed between filtrant beds (Galíndez et al, 2003). An indirect proof of adaptive remodelling of the splenic microarchitecture in armadillos, is the fact that new-borns of C. villosus, have a myeloid spleen without trabeculae .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This fact agrees with the splenic structure observed in D. novemcinctus (Hayes, 1970) and D. hybridus (Galíndez et al, 2000) and differs from the observed in Z. pichiy, which shows isolated smooth muscle cells and myofibroblasts interposed between filtrant beds (Galíndez et al, 2003). An indirect proof of adaptive remodelling of the splenic microarchitecture in armadillos, is the fact that new-borns of C. villosus, have a myeloid spleen without trabeculae .…”
Section: Discussionsupporting
confidence: 87%
“…The intermediate zone has narrow borders than the other studied Euphractini (Galíndez et al, , 2000(Galíndez et al, , 2003, and differs from rabbits and rodents (Blue & Weiss, 1981). The presence of macrophages Perls (+), ellipsoids and a discrete amount of vasculature, make this structure very similar to that present in the ancestral group Insectivora (Tanaka, 1990) and is, probably, the place for blood clearance.…”
Section: Discussionmentioning
confidence: 87%
“…The sinusal type of spleens was reported in rats, humans and dogs (Press & Landsverk, ; Udroiu, ; Ward et al, ). Mice along with various mammals such as horses, cows, cats, pigs and armadillos were classified to have the non‐sinusal type of spleen (Bacha & Bacha, ; Galíndez, Codón, & Casanave, ; Press & Landsverk, ; Snook, ; Ward et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…That the originator bacillus is genetically identical to the human bacillus (Opromolla et al, 1980;Meier et al, 1983). The armadillos show adaptive and primitive characteristics in both anatomical and physiological aspects (Galíndez et al, 2000).…”
Section: Introductionmentioning
confidence: 99%